Integrating Artificial Intelligence as an Advanced Learning Tool into Ukrainian Inclusive Educational Environment - Liliia Potapiuk; Alina Sasiuk (Освітологічний дискурс)
Artificial intelligence (AI) is increasingly recognized as an advanced educational tool, supported by substantial evidence demonstrating its effectiveness in addressing educational challenges of varying complexity — from generating lesson plans with a single click to facilitating virtual excursions within classroom settings. Despite the current monopolistic tendencies among companies producing artificial assistive technologies, the digital market is anticipated to soon become saturated with a diverse array of generative agents of any needs and wallets. In the context of general pedagogy, positive trends in AI integration are evident. However, inclusive education remains largely anchored in traditional pedagogical approaches, primarily due to the challenges associated with making significant advancements in this low-mobility sector. Before any innovative steps can be undertaken, fundamental material needs must be addressed. A comparative analysis of the Ukrainian inclusive education experience against international benchmarks reveals a notable regression since the onset of the full-scale invasion. While leading international initiatives are focused on the potential of AI to address global educational challenges, Ukraine appears to depend largely on the initiatives of individual educators. To explore the contentious issue of whether it is acceptable to disregard certain recommendations from prominent state and international institutions regarding the safe integration of AI into educational practices — especially in the absence of alternative validated methodologies for teaching children with special educational needs — a survey was conducted involving 43 respondents engaged in inclusive education. The findings affirm that the negative perceptions surrounding AI in inclusive contexts are justified: Ukraine's educational landscape is still evolving to reach the technological standards observed in the early 2000s in other countries. This article also highlights the risks associated with the uncritical introduction of «radically new technologies» from the era of the first computers into educational settings without first ensuring compliance with four critical criteria: content accuracy, age appropriateness, relevance of pedagogical methods, and cultural and social suitability. While the article predominantly conveys a skeptical perspective on the feasibility of effectively integrating AI into the inclusive educational process, the authors do not intend to diminish national accomplishments. Instead, they advocate for a research trajectory that is genuinely pertinent: Ukraine's journey with AI should be collaborative, aiming to refine tools that empower, rather than replace, ensuring that «artificial inclusion» becomes a lived reality rather than a tick-box culture.